The life, work and death of Ludwig van Beethoven (Den Haag; Trianon-Theater; Netherlands, 2020)
Program for a film shown at the Trianon-Theater, Den Haag, March 25, 1927, accompanied by live music with orchestra directed by Henri Zeldenrust and Tony Haartman, and solo piano performed by Theo van der Pas and B. Bennett.